Lead-free alternative cation (Ethylammonium) in organometallic perovskites for thermoelectric applications - Dubey, Anusha; Pandit, Naincy; Singh, Rashmi; Joshi, Tarun Kumar; Choudhary, Banwari Lal; Kamlesh, Peeyush Kumar; Al-Qaisi, Samah; Kumar, Tanuj; Kaur, Kulwinder; Verma, Ajay Singh (Journal of molecular modeling, 2024)
Context Hybrid halide perovskites are gaining prominence as a promising option in the advancement of photovoltaic devices. Ethylammonium-based hybrid halide perovskites have demonstrated impressive characteristics, such as a reduced band gap, enhanced stability, and non-toxic properties. In this study, we have explored the structural, electronic, optical, and thermoelectric characteristics of Ethylammonium tin chloride. We have found that Ethylammonium tin chloride (EASnCl 3 ) is a direct wide band gap semiconductor. Additionally, we conducted calculations for various optical parameters, including the dielectric function, absorption coefficient, and refractive index, across a photon energy spectrum ranging from 0 to 7 eV. The research highlights the exceptional qualities of EASnCl 3 , which exhibits a high absorption coefficient and an elevated Seeback coefficient, among other favorable attributes. These findings position it as a promising material for cost-effective photovoltaic device applications, addressing concerns related to environmental stability. Methods Fundamental properties based on the full-potential linearized augmented plane wave (FP-LAPW) method, this computation was performed using the WIEN2k simulation code. We utilized the exchange–correlation potentials PBE-GGA and KTB-mBJ to compute the optimized structure, density of states, and band structure of the material. In order to calculate the thermoelectric properties of the material, the Boltztrap simulation tool has been used. There are several critical absorbance parameters, including the Seeback coefficient, figure of merit, power factor, electrical conductivity, and thermal conductivity, concerning their carrier concentration and chemical potential, that have been taken into consideration.